Workshop Penggunaan Learning Apps dan Word Wall sebagai Media Pembelajaran Anak Usia Dini Bagi Guru - Wulandari, Hayani; Nazhifah, Nauroh; Azizah, Hasna Ainnur; Sholihatunnisa, Rina Nur; Andriyani, Wina Windiyanti (STMIK Royal, 2024)
The application of interactive learning media to improve the learning experience for children can be through introducing technology to early childhood. A strategy for teachers to develop this understanding and ability is that teachers can take part in training regarding digital learning media. Training regarding learning media was held at TK Yos Sudarso Purwakarta with the learning media used were Learning Apps and Wordwall. Methods uses in this training are Andragogy method with 3 stages, namely Planning, Implementation, and Evaluation. The results of this service ran smoothly, the learning media training participants were able to understand and complete the training activities well and succeeded in creating digital games using the Learning Apps and Word Wall platforms. Participants gave positive responses to the results of the training that had been carried out and hoped that the use of digital media could expand fun learning strategies in early childhood education. Keywords: early childhood education; interactive learning media; digital technology